THE EFFECT OF COMMON EUROPEAN ASYLUM SYSTEM (CEAS) ON NIGERIAN IRREGULAR MIGRANTS - Irabor, Peter (Torun International Studies, 2025)
The Common European Asylum System (CEAS) focused on the harmonisation and procedure for granting asylum to eligible migrants and safeguarding the rights of those in need of protection across European Union (EU) member states. This study appraised the performance of CEAS on Nigerian irregular migrants and examined the challenges of CEAS for them. The study relied on qualitative data through Individual In-depth Interviews (IDIs) conducted on representatives from European External Action Service, European Union’s delegation to Nigeria and ECOWAS, Frontex, International Organisation for Migration, Nigeria Immigration Service, Idia Renaissance, and the National Agency for the Prohibition of Trafficking in Persons. Preliminary findings showed that majority of Nigerian irregular migrants seeking asylum are not necessarily refugees but economic migrants who seek better life in Europe and, due to this, they change their nationality and give false impression in order to be granted asylum. The difficulty for the EU immigration officials to establish evidence regarding their true identity makes it possible for Nigerian irregular migrants to remain in reception centres for a longer period; some of them do not wait to complete their biometric registration, while others deliberately withdraw asylum applications in order to abscond and reapply in different EU countries. Some of the challenges of CEAS for Nigerian irregular migrants, according to the findings, include slow handling of asylum requests, which consequently led to overcrowded reception centres, conflicting interests of EU member states regarding commitment and procedure of CEAS, as well as strict asylum procedure, which violate the rule of law and rights of migrants who seek genuine protection in EU member states. This study concluded that the handling of CEAS has resulted in the increase of Nigerian irregular migrants that applied for asylum, consequently increasing the number of pending asylum applications across Europe.